Secondary Metabolites from the Mangrove-derived Fungus Trichoderma sp. - Zi, Guangrong; Shi, Ying; Hong, Kui; Liu, Ling (Natural Products Journal, The, 2025)
BackgroundSecondary metabolites from the mangrove-derived fungi have great potential to produce natural products with novel structures and significant biological activities.ObjectiveThe objective of this study was to isolate and identify the secondary metabolites from the mangrove-derived fungus Trichoderma sp. WHUF0342, and evaluate their antibacterial activities.MethodsThe compounds were isolated and purified by silica gel column chromatography, Sephadex LH-20 gel chromatography, and semi-preparative high-performance liquid chromatography (HPLC). Their structures were elucidated by comparing the NMR and MS spectroscopic data with those of literature. The antibacterial activity were evaluated by modified broth microdilution assay.ResultsEight compounds were isolated from the fermented extracts of the fungus Trichoderma sp. WHUF0342 and identified as chaxine B (1), nafuredin (2), dichlorodiaportin (3), ferulaic acid (4), bis(2-ethylhexyl) benzene-1,2-dicarboxylate (5), methyl 4-hydroxyphenylacetate (6), 4-hydroxyphenyl acetate (7), and 4-hydroxyphenylethyl acetate (8). Chaxine B (1) showed antibacterial activity against the phytopathogenic bacterium Ralstonia solanacearum with a minimum inhibitory concentration (MIC) value of 16 μg/mL. The antibacterial activity against plant pathogen of compound 1 was reported for the first time in this study.ConclusionThis study not only enriched the secondary metabolites of mangrove-derived fungi but also provided a valuable resource for the prevention of agricultural pathogen infections.
Keywords: Trichoderma sp.